Question
upstudy study bank question image url

Let \( f(x)=x^{2}+4 x \) (A) Find the slope of the secant line from \( x=3 \) to \( x=9 \). Slope of secant line \( =16 \) (B) Find the equation of the secant line from \( x=3 \) to \( x=9 \). \( y=\square \) (C) Find the slope of the secant line from \( x=3 \) to \( x=6 \). Slope of secant line \( =\square \) (D) Find the equation of the secant line from \( x=3 \) to \( x=6 \). \( y=\square \)

Ask by Gordon Owen. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**(B)** \( y = 16x - 27 \) **(C)** Slope of the secant line \( = 13 \) **(D)** \( y = 13x - 18 \)

Solution

Let's solve each part of the problem step by step. Given the function: \[ f(x) = x^{2} + 4x \] ### (A) Slope of the Secant Line from \( x = 3 \) to \( x = 9 \) You've already correctly calculated this: \[ \text{Slope} = 16 \] --- ### (B) Equation of the Secant Line from \( x = 3 \) to \( x = 9 \) **Step 1: Find the coordinates of the two points.** - At \( x = 3 \): \[ f(3) = 3^{2} + 4(3) = 9 + 12 = 21 \] So, the point is \( (3, 21) \). - At \( x = 9 \): \[ f(9) = 9^{2} + 4(9) = 81 + 36 = 117 \] So, the point is \( (9, 117) \). **Step 2: Use the point-slope form of a line.** The slope (\( m \)) is already known to be 16. Using the point \( (3, 21) \): \[ y - y_{1} = m(x - x_{1}) \\ y - 21 = 16(x - 3) \\ y - 21 = 16x - 48 \\ y = 16x - 48 + 21 \\ y = 16x - 27 \] **Answer:** \[ y = 16x - 27 \] --- ### (C) Slope of the Secant Line from \( x = 3 \) to \( x = 6 \) **Step 1: Find the coordinates of the two points.** - At \( x = 3 \): \[ f(3) = 3^{2} + 4(3) = 9 + 12 = 21 \] So, the point is \( (3, 21) \). - At \( x = 6 \): \[ f(6) = 6^{2} + 4(6) = 36 + 24 = 60 \] So, the point is \( (6, 60) \). **Step 2: Calculate the slope (\( m \)).** \[ m = \frac{f(6) - f(3)}{6 - 3} = \frac{60 - 21}{3} = \frac{39}{3} = 13 \] **Answer:** \[ \text{Slope of secant line} = 13 \] --- ### (D) Equation of the Secant Line from \( x = 3 \) to \( x = 6 \) **Using the Point-Slope Form:** The slope (\( m \)) is 13, and we can use the point \( (3, 21) \). \[ y - y_{1} = m(x - x_{1}) \\ y - 21 = 13(x - 3) \\ y - 21 = 13x - 39 \\ y = 13x - 39 + 21 \\ y = 13x - 18 \] **Answer:** \[ y = 13x - 18 \] --- ### Summary of Answers - **(B)** \( y = 16x - 27 \) - **(C)** Slope of the secant line \( = 13 \) - **(D)** \( y = 13x - 18 \)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To solve the problems step-by-step, let’s first tackle part (A). (A) To find the slope of the secant line from \( x = 3 \) to \( x = 9 \), we need to calculate the values of the function at these points. 1. Calculate \( f(3) \): \[ f(3) = 3^2 + 4(3) = 9 + 12 = 21 \] 2. Calculate \( f(9) \): \[ f(9) = 9^2 + 4(9) = 81 + 36 = 117 \] 3. The slope of the secant line is given by the formula: \[ \text{slope} = \frac{f(9) - f(3)}{9 - 3} = \frac{117 - 21}{9 - 3} = \frac{96}{6} = 16 \] So the slope of the secant line from \( x=3 \) to \( x=9 \) is \( 16 \). (B) Next, we need to find the equation of the secant line. We can use the point-slope form of the line equation. The slope we found is \( 16 \), and we can use the point \( (3, 21) \) to find the equation: \[ y - 21 = 16(x - 3) \] Distributing the slope: \[ y - 21 = 16x - 48 \] Adding \( 21 \) to both sides: \[ y = 16x - 27 \] Thus, the equation of the secant line from \( x=3 \) to \( x=9 \) is \( y = 16x - 27 \). (C) Now, let's find the slope of the secant line from \( x = 3 \) to \( x = 6 \). 1. Calculate \( f(6) \): \[ f(6) = 6^2 + 4(6) = 36 + 24 = 60 \] 2. The slope of the secant line is given by: \[ \text{slope} = \frac{f(6) - f(3)}{6 - 3} = \frac{60 - 21}{6 - 3} = \frac{39}{3} = 13 \] So the slope of the secant line from \( x=3 \) to \( x=6 \) is \( 13 \). (D) Now, let’s find the equation of the secant line from \( x=3 \) to \( x=6 \). Using the slope we've found (which is \( 13 \)) and the point \( (3, 21) \): \[ y - 21 = 13(x - 3) \] Distributing: \[ y - 21 = 13x - 39 \] Adding \( 21 \) to both sides: \[ y = 13x - 18 \] Thus, the equation of the secant line from \( x=3 \) to \( x=6 \) is \( y = 13x - 18 \). In summary: (A) Slope of secant line \( = 16 \) (B) Equation: \( y = 16x - 27 \) (C) Slope of secant line \( = 13 \) (D) Equation: \( y = 13x - 18 \)

Related Questions

Latest Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy